Familial Myelodysplastic/Acute Leukemia Syndromes—Myeloid Neoplasms with Germline Predisposition - Baptista, Renata Lyrio Rafael; dos Santos, Anna Cláudia Evangelista; Gutiyama, Luciana Mayumi; Solza, Cristiana; Zalcberg, Ilana Renault (Frontiers in Oncology, 2017)
Although most cases of myeloid neoplasms are sporadic, a small subset has been associated with germline mutations. The 2016 revision of the World Health Organization (WHO) classification included these cases in a myeloid neoplasm group with a predisposing germline mutational background. These patients must have a different management and their families should get genetic counseling. Cases identification and outline of the major known syndromes characteristics will be discussed in this text.